Parceling as an object of study in modern linguistic literature - GURIEVA, NATALIA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article parceling is analyzed as the object of linguistic research, the paper outlines the history of the issue, promising areas of study parzellierung designs in modern linguistics on the material of texts of different stylistic and genre focus, including functions parzellierung designs in the Orthodox newspaper journalism.
Keywords: parceling, parallelomania designs, parcelled, communicative and expressivestylistic organization of speech, artistic speech, journalistic speech